MISANDRY IN ANNE STEVENSONS POEM "THE VICTORY": A PSCHOANALYTIC FEMINIST STUDY - Widiyanto, M wahyu; Kustantinah, Indri; Astria, Isana (ETERNAL, 2011)
This literary analysis of Anne Stevensonâs poem âThe Victoryâ answers the factors which triggering misandry, how misandry is described in the poem and what impacts of misandry toward âIâ and her baby in the poem. This research is carried by some theories of feminism and psychoanalysis. âThe Victoryâ poem tells about misandry which means hatred toward men as a sex. The woman hates the man who has done her sexual aggression in a manner brutal and hideous. Factors trigger a womans hatred is a male dominated society makes men think that they have privilege and power over women either physically or psychologically that stimulates them to legalize oppression among women. And the impact of misandry towards the "I" and her baby in the poem are postpartum depression, mothers neglect to love her baby, and tendency to do child abuse or harm her own baby, while the impact for the baby itsef is that he would accept less affection from his mother and the tendency to do misoginy towards women in the future as the manifestation of his life experience. The conclusion is that Misandry comes from gynocentric use of gender in a male dominated society. A male dominated society makes men think that they have privilege and power over women either physically or psychologically that stimulates them to legalize oppression among women. Those women who feel oppressed and aggressed either physically and psychologically think that this is an unjust treatment upon them that makes them unite and gather to defend and protect themselves from mens unjust treatment under a terminology called "misandry".